Grounding Anger Management - Odis E. Simmons (Grounded Theory Review: An International Journal, 2017)
One of the things that drew me to grounded theory from the beginning was Glaser and Strauss’ assertion in The Discovery of Grounded Theory that it was useful as a “theoretical foothold” for practical applications (p. 268). From this, when I was a Ph.D student studying under Glaser and Strauss in the early 1970s, I devised a GT based approach to action I later came to call “grounded action.” In this short paper I’ll present a very brief sketch of an anger management program I developed in 1992, using grounded action. I began my research by attending a two-day anger management training workshop designed for training professionals in the most commonly used anger management model. Like other intervention programs I had seen, this model took a psychologizing and pathologizing approach to the issue. Following this, I sat through the full course of an anger management program that used this model, observing the reactions of the participants and the approach of the facilitator. Following each session I conducted open-ended interviews with most of the participants, either individually or in groups of two or three. I had also done previous research in counseling and social work contexts that turned out to be very relevant to an anger management program design.